Advances in Technologies for Purification and Enrichment of Extracellular Vesicles. (October 2019) - Zhang, Pan; Yeo, Joo Chuan; Lim, Chwee Teck
Extracellular vesicles (EVs) are lipid bilayer-bound vesicles secreted by cells. Subtypes of EVs such as microvesicles and exosomes are further categorized mainly by their different biogenesis mechanisms. EVs have been revealed to play an important role in disease diagnosis and intercellular communication. Despite the wide interest in EVs, the technologies for the purification and enrichment of EVs are still in their infancy. The isolation of EVs, especially exosomes, is inherently challenging due to their small size and heterogeneity. In this review, we mainly introduce the advances of techniques in isolating microvesicles and exosomes according to their approaches. Also, we discuss the limitations of currently reported technologies in terms of their specificity and efficiency, and provide our thoughts about future developments of EV purification and enrichment technology.